Fractionation of Lead and Cadmium in Refuse Dump Soil Treated With Cassava Mill Effluent - Ndiokwere, C. L. (Journal of Agriculture and Environment, 2009)
The effect of application of cassava (Manihot esculenta) processing mill effluent (CME) on the chemical fractionation of lead (Pb) and cadmium (Cd) in soil obtained from a refuse dump site was assessed in this study. Selected physiochemical properties of the soil and CME were determined while four different amounts of the CME were applied to the soil. The refuse dump soil had average pH of 6.2, while the cation exchange capacity was dominated by calcium. Similarly, the CME had a mean pH of 4.21 and high mean phosphorus concentration of 3160mg/kg. Chemical fractionation of the soil not containing CME showed 58.65 and 7.90mg/kg of Pb and Cd respectively in the carbonate fraction. Following the application of CME, there was redistribution of Pb and Cd in the different fractions. CME contributed to increase Cd amount in the carbonate fraction, while the residual fraction had almost uniform distribution of Cd with the various treatments of CME. However, the result indicated that depending on the applied amount of the CME there was an overall reduction in the concentration of Pb in the different fraction, while there were corresponding increases for Cd amongst the various fractions in the soil. Key words: Chemical fractionation, lead, cadmium, dump soil, cassava mill-effluent, cation exchange. The Journal of Agriculture and Environment Vol:9, Jun.2008 Page: 10-15